Aronia Upregulates Myogenic Differentiation and Augments Muscle Mass and Function Through Muscle Metabolism - Yun, Chae-Eun; So, Hyun-Kyung; Vuong, Tuan Anh; Na, Myung Woo; Anh, Subin; Lee, Hyo-Keun; Kim, Ki Hyun; Kang, Jong-Sun; Bae, Gyu-Un; Lee, Sang-Jin (Frontiers in Nutrition, 2021)
Black chokeberry or aronia (the fruit of Aronia melanocarpa) has been reported to having pharmacological activities against metabolic syndrome, such as hypertension, obesity, diabetes, and pro-inflammatory conditions. However, the effects of aronia on myogenic differentiation and muscle homoeostasis are uncharacterized. In this study, we investigated the effects of aronia (black chokeberry) on myogenic differentiation and muscle metabolic functions in young mice. Aronia extract (AR) promotes myogenic differentiation and elevates the formation of multinucleated myotubes through Akt activation. AR protects dexamethasone (DEX)-induced myotube atrophy through inhibition of muscle-specific ubiquitin ligases mediated by Akt activation. The treatment with AR increases muscle mass and strength in mice without cardiac hypertrophy. AR treatment enhances both oxidative and glycolytic myofibers and muscle metabolism with elevated mitochondrial genes and glucose metabolism-related genes. Furthermore, AR-fed muscle fibers display increased levels of total OxPHOS and myoglobin proteins. Taken together, AR enhances myogenic differentiation and improves muscle mass and function, suggesting that AR has a promising potential as a nutraceutical remedy to intervene in muscle weakness and atrophy.